2020
DOI: 10.1101/2020.01.21.20017988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Family Presence and Audience Effects on Cardiopulmonary Resuscitation: Perceptions of Pre-hospital Emergency Caregivers in Turkey

Abstract: Background: There have been many studies regarding family presence during cardiopulmonary resuscitation and most of them are about emergency services or intensive care units. However, the issue has not been studied enough in terms of pre-hospital emergency medicine and the perspective of pre-hospital emergency caregivers. Aim: In this study, it is aimed to present the perceptions and attitudes of a group of pre-hospital emergency care professionals to family presence during cardiopulmonary resuscitation. Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…The results showed that the score of the personnel members' attitudes towards FPDR was lower than the mean value. These results are in line with the results of the studies which were conducted in Turkey [11] and Portugal [33] which they reported that the majority of prehospital emergency personnel members disagreed with the family presence during resuscitation. Furthermore, the results of other studies have indicated that most of the EMS team members do not prefer to provide resuscitation in the presence of the patents' family members and a large number of them feel uncomfortable about resuscitating the patients in the presence of their family members [9,10].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results showed that the score of the personnel members' attitudes towards FPDR was lower than the mean value. These results are in line with the results of the studies which were conducted in Turkey [11] and Portugal [33] which they reported that the majority of prehospital emergency personnel members disagreed with the family presence during resuscitation. Furthermore, the results of other studies have indicated that most of the EMS team members do not prefer to provide resuscitation in the presence of the patents' family members and a large number of them feel uncomfortable about resuscitating the patients in the presence of their family members [9,10].…”
Section: Discussionsupporting
confidence: 89%
“…This statistic was 87% in France [9] and 95.3% in the United States of America [10]. These results show that the presence of family members during the patients' prehospital resuscitation is very common and the personnel members have considerable experience of resuscitation in the presence of the patients' family members [9][10][11]. Therefore, these experiences can be used to develop training guidelines for the personnel in order to support the patients' family members during their resuscitation in prehospital emergency.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations